2012
DOI: 10.1007/s11357-012-9486-7
|View full text |Cite
|
Sign up to set email alerts
|

Physically active vs. inactive lifestyle, muscle properties, and glucose homeostasis in middle-aged and older twins

Abstract: Exercise-induced positive changes in skeletal muscle properties and metabolism decrease the risk for disability, cardiometabolic diseases and mortality. Here, we studied muscle properties and glucose homeostasis in a non-exercise stage in twin pairs with cotwins discordant for physical activity habits for at least 32 years of their adult lives. Isometric knee extension force, MR imaging of midthigh tissue composition and muscle volume, and fasting blood samples were acquired from 16 same-sex (seven monozygotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 49 publications
(76 reference statements)
2
24
0
Order By: Relevance
“…Similarly, we now conclude that thigh IMAT is the stronger contributor to cardiometabolic dysfunction. Our findings agree with other research studies that significant relations exist between IMAT in the thigh and glucose [ 8 , 13 , 21 , 38 ], insulin [ 21 , 39 ], and HOMA-IR [ 6 , 39 ]. While mechanistic support is lacking and some research studies do not support the relation between IMAT and markers of glucose control [ 33 , 40 ], our results support the preponderance of research suggesting that IMAT contributes to (or is a product of) disrupted glucose homeostasis [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, we now conclude that thigh IMAT is the stronger contributor to cardiometabolic dysfunction. Our findings agree with other research studies that significant relations exist between IMAT in the thigh and glucose [ 8 , 13 , 21 , 38 ], insulin [ 21 , 39 ], and HOMA-IR [ 6 , 39 ]. While mechanistic support is lacking and some research studies do not support the relation between IMAT and markers of glucose control [ 33 , 40 ], our results support the preponderance of research suggesting that IMAT contributes to (or is a product of) disrupted glucose homeostasis [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Often, sections of the lower limbs are analyzed by magnetic resonance imaging (MRI) or computed tomography to quantify relative IMAT content. These sections of either the thigh [ 15 , 17 21 ] or calf [ 12 , 13 , 22 , 23 ] are often interpreted as being representative of whole-body muscle composition. However, IMAT infiltration into skeletal muscle may be muscle- or muscle-compartment specific [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors considered have established links to impairment in physical function, and there are proposed biological mechanisms that could explain their effects on muscle function and loss of muscle mass and strength in older adults. 4,5,[30][31][32][33] Although membership of the Hertfordshire cohort was defined according to area of birth and residence, and there has been loss to follow-up, the participants' characteristics are comparable with those of the wider community. 21 Although a priori-defined cutoffs were used to identify groups of participants who were inactive or whose diet was poor using calculated physical activity and dietary scores, sensitivity analyses showed that changing these cutoffs did not alter the strong association between increasing number of risk factors and poorer physical function.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of IMAT are associated with insulin resistance [5, 6, 8, 14, 28, 3436], a loss of strength [2331], and mobility dysfunction [23, 4143]. High levels of IMAT can be found in many patient populations, including, but not restricted to, the paraspinal muscles of individuals with chronic back pain [37, 38] and the locomotor muscles of individuals diagnosed with HIV [44], spinal cord injury [39], CVA [40], diabetes [6], and COPD [45].…”
Section: Introductionmentioning
confidence: 99%